The influence factors and perceptions towards the student performance and the tendency to choose public relations course / Siti Nirmala Mohamad Ishak and Abdul Rauf Ridzuan - Mohamad Ishak, Siti Nirmala; Ridzuan, Abdul Rauf (Faculty of Communication & Media Studies, 2019)
The ultimate aim of Public Relations is to present organizations in the best light possible. This requires special skills in the area of research, managerial, persuasive communication, strategic planning and writing. The standpoint is needed to evaluate the progressive of the profession growth in the industry. Public Relations itself can be a best platform for a person to represent themselves and express their interest towards the profession. This research examined the study of factors and perceptions towards the student’s school and academic performances and their tendency to choose Public Relations course as the main options. The amount of survey calculated based on Krejcie and Morgan Table, N=95 , S=76 by using purposive sampling method. Descriptive quantitative research study was conducted through survey using questionnaire form. The hypothesis testing gained by using two different methods which indicated different result which are Pearson Correlation and Multiple Linear Regression. Based on the research by using Pearson Correlation method, the five listed null hypothesis is accepted based on the standardized significant values which is must be or less than 0.05. However, based on Multiple Linear Regression method, there is different reading which formed different results. Based on significant value in Coefficient Multiple Linear Regression analysis, the null hypothesis of self-interest (0.042) and industry prospect (0.037) is being accepted with significant value below than 0.05.